UTILISASI E-GOVERNMENT MALANG KABUPATEN TOURISM INTELLIGENCE CENTER (MATIC) DALAM UPAYA OPTIMALISASI KUNJUNGAN PANTAI BALEKAMBANG - Moch Erwin Saputro; Hayat; Hirshi Anadza (Halu Oleo University, 2025)
This study aims to analyse the utilisation of the Malang Kabupaten Tourism Intelligence Centre (MATIC) platform in optimising tourist visits to Balekambang Beach. MATIC is an e-government innovation based on big data and smart tourism, developed by DISPARBUD Malang Regency, to digitise tourism information and support collaboration among stakeholders. This research employs a qualitative descriptive approach using the e-Government implementation theory, which includes the aspects of support, capacity, and value. The findings show that while MATIC offers superior features such as destination QR Codes, product catalogues, tourism agendas, and visitor statistics, its utilisation remains limited. Supporting factors include budgetary support, human resource training, and digital infrastructure. However, the inhibiting factors consist of a lack of outreach, low digital literacy among tourism actors, accessibility issues to the location, and insufficient synergy between MATIC and social media promotion. Therefore, optimising MATIC requires a comprehensive strategy that involves technical improvements, capacity building, and cross-sector digital promotion collaboration.